Single Atrium Repair with Delayed Sternal Closure in a Postpartum Multiparous Woman: A Case Report - Jianing Wang; Huimin Shao; Can Xu; Dongjin Wang (Journal of Clinical Medicine, 2026)
Background/Objectives: Single atrium is a rare congenital heart defect typically repaired in infancy. Unrepaired adults with pregnancy face high risk, and postpartum repair with delayed sternal closure (DSC) has rarely been reported. Methods: We present a 33-year-old multiparous woman who presented at 30 weeks + 1 day of gestation with progressive dyspnea. Transthoracic echocardiography (TTE) revealed a single atrium with a common atrioventricular valve and an estimated pulmonary artery systolic pressure (PASP) of 47 mmHg. The multidisciplinary team advised early cesarean section, which was performed at 30 weeks + 3 days of gestation, but postpartum symptoms persisted. Six months later, the patient underwent surgical correction. The procedure was converted from right subaxillary mini-thoracotomy to median sternotomy due to intraoperative aortic dissection, which was repaired. The single atrium was partitioned using a bovine pericardial patch. Due to myocardial edema and hemodynamic instability, the sternum was left open and closed on postoperative day 4. She required 8 days of mechanical ventilation and 13 days of intensive care, and was discharged on day 27. Results: Surgical repair was successful, and at the 6-month postoperative follow-up, she had achieved NYHA class I functional status, with an estimated PASP of 40 mmHg and a well-positioned baffle with no residual shunt. Conclusions: This case demonstrates that multidisciplinary collaboration is essential for pregnant patients with unrepaired congenital heart disease, postpartum surgical correction is feasible with careful perioperative planning, and DSC is a safe strategy for managing hemodynamic instability in complex cardiac cases.